Food safety chemistry : toxicant occurrence, analysis and mitigation - Yu, Liangli; Wang, Shuo, 1969-; Sun, Baoguo, 1961- (CRC Press, 2015)
"This edited book is a comprehensive guide to the chemistry of food toxicants produced during processing, formulation, and storage of food. Each major food chemical contaminant will be discussed for toxic effects and the biological mechanisms behind their toxicity. Their absorption and distribution profiles and the factors influencing their levels in foods will be discussed. In addition, a listing of commonly used analytical techniques in food safety chemistry will make the book useful for food scientists and nutritionists"-- Provided by publisher.
Keywords: Food adulteration and inspection.; Food contamination.; Food -- Analysis.; Food -- Microbiology.; elektronické knihy; electronic books